ZAMONAVIY O‘ZBEK ADABIYOTIDA O‘QITUVCHI-ZIYOLI OBRAZI TALQINLARI - Soberova, Mohira (FILOLOGIYA UFQLARI JURNALI, 2024)
The article examines the interpretation of the image of a teacher-intellectual in modern Uzbek literature using the examples of writers such as Fitrat, Behbudi, Cholpon, and Abdulla Qahhor. Their unique style and skills in creating the images of teacher, teacher-intellectual were noted in the process of analysis.